Approaching Kautaliya Arthashastra from the Communication Perspective - Adhikary, Nirmala Mani (Bodhi: An Interdisciplinary Journal, 2023)
Political thoughts on good governance from the Hindu perspective are set by Dandaniti, which is guided by Dharma and Artha in a continuum. Kautilya’s Arthashastra has been one of the most influential sources of political thoughts in Hinduism since over two millennia. The treatise deals with wide-ranging subject matters including politics, economics, governance, administration, philosophy, and so on. Though the emphasis on Artha is self-evident in Arthashastra, the common guiding principle for all affairs of statecraft as envisioned by Kautilya is the concept of Dharma. For instance, raja-dharma, the duty of the King or the ruler, is discussed at length in the classic text. As evident in Arthashastra, Hinduism envisions close interconnection between peace, politics and religion, in which politics guided by Dharma is instrumental for ensuring peace in society. This classical treatise can be approached from the communication perspective, employing certain indicators.